2014
DOI: 10.1108/jea-09-2012-0103
|View full text |Cite
|
Sign up to set email alerts
|

The timeline of self-efficacy: changes during the professional life cycle of school principals

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
(49 reference statements)
1
24
2
1
Order By: Relevance
“…Bandura (1997) suggested that self-efficacy develops based on a variety of experiences suggesting the greater the experiences the higher the level of efficacy. Fisher (2014) found efficacy levels highest during the first year as principal with a significant drop in the years 2-5. Efficacy levels then increased after the fifth year and stabilized at year 10.…”
Section: Empirical Evidence On Principal Self-efficacymentioning
confidence: 89%
See 2 more Smart Citations
“…Bandura (1997) suggested that self-efficacy develops based on a variety of experiences suggesting the greater the experiences the higher the level of efficacy. Fisher (2014) found efficacy levels highest during the first year as principal with a significant drop in the years 2-5. Efficacy levels then increased after the fifth year and stabilized at year 10.…”
Section: Empirical Evidence On Principal Self-efficacymentioning
confidence: 89%
“…The findings by Fisher (2014) show that PSE in fact drops over time and offer the possible explanation that principals in their first year are naive enough to think they still have total control over the events and activities required of the job.…”
Section: Empirical Evidence On Principal Self-efficacymentioning
confidence: 92%
See 1 more Smart Citation
“…Fisher (2014) found that principals reported their highest sense of efficacy in their first year as a principal, followed by a drop in the second through fifth years. Their sense of efficacy rose between the fifth and tenth year, leveling off and maintaining after the tenth year.…”
Section: Principal Self-efficacymentioning
confidence: 99%
“…In a more recent study of 123 Israeli principals surveyed with PSES, Fisher (2014) found that the sense of efficacy of principals changes throughout a principal's tenure. Fisher (2014) found that principals reported their highest sense of efficacy in their first year as a principal, followed by a drop in the second through fifth years.…”
Section: Principal Self-efficacymentioning
confidence: 99%